Nutritional analysis of indigenous sources: An approach to explore its potential application as alternative feedstuffs for Thai Koi (Anabas testudineus) - Md. Zia Uddin Al Mamun; Shyama Prosad Moulick; Mohajira Begum; Farhana Jahan; Mohammed A. Satter; Md. Nazim Uddin; Rahima Akter Sathee; Md. Waliullah; Faridul Islam (Journal of Agriculture and Food Research, 2023)
Aquaculture recently gained importance due to rising protein consumption and sustainable fisheries production. Any fish farm needs affordable, environmentally friendly feed to maximize profit. Bangladesh imports fish feed materials from neighboring countries at a considerable cost. Therefore, the present research aims to investigate the nutritive value of local organic resources and to evaluate their usage as feedstuffs thus reducing operational costs for Anabas testudineus (Thai koi) farming. The selected nineteen raw materials were subjected to proximate and minerals (Na, P, K, Ca, Fe) content analyses. The results revealed that each ingredient analyzed contains a substantial amount of protein (ranging from 6.07 to 58.76%). The recorded crude fat, moisture, ash, crude fiber, carbohydrate, and energy contents varied within a range of 0.46–14.78%, 1.40–9.95%, 1.19–81.50%, 0–41.77%, 5.33–71.17%, and 58.77–399.81 kcal/100g respectively. The ingredients also contain an appreciable amount of potassium (78.64–3718.32 mg/100g), calcium (1.20–37175.41 mg/100g), and phosphorous (7.92–258.97 mg/100g). The results demonstrate that the analyzed indigenous raw materials were high in nutritional value and mineral contents and thus could be used as potential substitute compositions for Thai koi feed formulation.